The Impact of Extension on Sheep Haemonchosis Treatment Using Mango Leaf Powder on Farmer Adoption Through Motion Graphics Videos In Ngipik Village, Pringsurat District - Nurdayati, Nurdayati; Ma’mun, Mukhammad Farkhan; Akbarrizki, Muzizat (Jurnal Penelitian Peternakan Terpadu, 2024)
This research was conducted in Ngipik Village, Temanggung District, Temanggung Regency. The study aimed to determine the influence of extension on sheep haemonchosis treatment using mango leaf powder on farmer adoption through motion graphics videos in Ngipik Village, Pringsurat District. The respondents used in this activity were 35 sheep farmers in Ngipik Village, selected using purposive sampling. The study design used the One Group Pretest-Posttest Design to measure the effect, with pretest data collected before the extension and posttest data collected after the extension through field visits and interviews using questionnaires. The data analysis methods used were descriptive analysis and statistical analysis using the Wilcoxon test. The effectiveness value of extension in making mango leaf powder for haemonchosis through motion graphics videos was 68.15, categorized as effective, while the effectiveness value of behavior change in sheep farmers was 33.83, categorized as moderately effective. The results of the Wilcoxon test analysis showed that there was a significant change (p<0.01) in the adoption stages (interest, awareness, evaluation, trial, and adoption) of farmers before and after the extension in making mango leaf powder for haemonchosis treatment in sheep through motion graphics videos in Ngipik Village, Pringsurat District.